2003
DOI: 10.1890/1051-0761(2003)013[0038:ihbnct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Introgressive Hybridization Between Native Cutthroat Trout and Introduced Rainbow Trout

Abstract: Introgressive hybridization threatens the persistence of several species of native salmonids in the western United States, but little is known about the factors influencing the establishment and maintenance of introgressed populations. We examined the occurrence of introgressive hybridization in westslope cutthroat (Oncorhynchus clarki lewisi) and rainbow trout (O. mykiss) populations in relation to physical characteristics of streams, trout density estimates, and the distance from stocking source. Trout were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 51 publications
9
93
2
Order By: Relevance
“…Indirect effects such as competitive displacement and/or hybridization are possible risks associated with the introduction of exotic species, including EPN (Ellstrand et al 1999, van Lenteren et al 2003, Weigel et al 2003. Strains of a species may differ in virulence, reproductive capacity, and environmental tolerance (Somasekhar et al 2002b), and there is a risk that exotic strains might competitively displace native strains of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect effects such as competitive displacement and/or hybridization are possible risks associated with the introduction of exotic species, including EPN (Ellstrand et al 1999, van Lenteren et al 2003, Weigel et al 2003. Strains of a species may differ in virulence, reproductive capacity, and environmental tolerance (Somasekhar et al 2002b), and there is a risk that exotic strains might competitively displace native strains of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…Perry et al (2002) provide a thorough discussion and review of hybridization in freshwater systems and suggested that hybridization is one of the most important factors associated with the poor status of aquatic organisms. For example, hybridization of cutthroat trout (Oncorhynchus clarki) with rainbow trout (0. mykiss) is a primary threat to the persistence of cutthroat trout (Weigel et al 2003). Similar concerns have been expressed for a variety of aquatic and terrestrial organisms (Rhymer and Simberloff 1996, Allendorf et al 2001, Perry et al 2002.…”
Section: Resultsmentioning
confidence: 83%
“…Recent studies of hybridization between other native and introduced salmonids have demonstrated that oftentimes the pattern of hybridization within a stream network is not random and that the extent of hybridization within a stream can be influenced by a number of biotic and abiotic factors (Weigel et al 2003;Bettles et al 2005;Rubidge and Taylor 2005;Boyer et al 2008;Gunnell et al 2008). Given these results, a more thorough examination of the spatial patterns of hybridization between bull trout and brook trout is warranted.…”
Section: Redband Studymentioning
confidence: 99%